# FTC saves the day!

Problem-1 Given

$f(x) = \int\limits_{0}^{2x}f(\frac{t}{2})\;dt +\log(2)\quad\quad\quad(\star)$

where $f(x)$ is a continuous function, find $f(x).$

Solution

Let

$p=2x \implies \frac{dp}{dx} = 2.\quad\quad\quad(1-1)$

By $(\star)$,

$\frac{df(x)}{dx} =\frac{d}{dx} \int\limits_{0}^{p} f(\frac{t}{2})\;dt + \frac{d\log(2)}{dx} = \underline{\frac{d}{dp}\left(\int\limits_{0}^{p} f(\frac{t}{2})\;dt\right)} \cdot \frac{dp}{dx}\overset{\textbf{FTC}}{=}\underline{f(\frac{p}{2})}\cdot \frac{dp}{dx}\overset{(1-1)}{=}2f(x),$

i.e.,

$\frac{df(x)}{dx} = 2f(x).\quad\quad\quad(1-2)$

Moreover, we see from $(\star)$ that

$f(0) = \int\limits_{0}^{0}f(\frac{t}{2})\;dt + \log(2) = 0 + \log(2) = \log(2).\quad\quad\quad(1-3)$

Solving initial-value problem

$\begin{cases} \frac{df(x)}{dx} = 2f(x)\\ f(0)=\log(2)\end{cases}$

gives

$f(x) = \log(2)\cdot e^{2x}.$

We use Omega CAS Explorer to verify:

Fig. 1-1

Problem-2 Given

$\int\limits_{0}^{1}f(u\cdot x) \;du = \frac{1}{2} f(x) +1\quad\quad\quad(\star\star)$

where $f(x)$ is a continuous function, find $f(x).$

Solution

Let $p=u\cdot x,$

$u=\frac{p}{x} \implies \frac{du}{dp} = \frac{1}{x}\quad\quad\quad(2-1)$

$u=0\implies p=0; u=1\implies p=x.\quad\quad\quad(2-2)$

$\int\limits_{0}^{1}f(u\cdot x)\;du\overset{(2)}{=} \int\limits_{0}^{x}f(p)\cdot\frac{du}{dp}\cdot dp\overset{(1)}{=}\int\limits_{0}^{x}f(p)\frac{1}{x}\;dp=\frac{1}{x}\int\limits_{0}^{x}f(p)\;dp.\quad\quad\quad(2-3)$

By (2-3), we express $(\star\star)$ as

$\frac{1}{x}\int\limits_{0}^{x}f(p)\;dp = \frac{1}{2}f(x)+1,$

i.e.,

$\int\limits_{0}^{x} f(p)\;dp = \frac{x}{2}f(x)+x.$

It follows that

$\underline{\frac{d}{dx}\left(\int\limits_{0}^{x}f(p)\;dp\right)}=\frac{d}{dx}\left(\frac{x}{2}f(x)+x\right)\overset{\textbf{FTC}}{\implies}\underline{f(x)}=\frac{1}{2}\left(f(x) + x\frac{d f(x)}{dx}\right)+1.\;(2-4)$

Solving differential equation (2-4) (see Fig. 2-1) gives

$f(x) = c x + 2.$

Fig. 2-1

The solution is verified by Omega CAS Explorer:

Fig. 2-2

Exercise-1 Solving $\begin{cases} \frac{df(x)}{dx} = 2f(x)\\ f(0)=\log(2)\end{cases}$ using a CAS.

Exercise-2 Solving (2-4) without using a CAS.

# An Epilogue to “Truth vs. Intellect”

This post illustrates an alternative of compute the approximate value of $\pi$.

We begin with a circle whose radius is $r$, and let $L_{n}, L_{n+1}$ denotes the side’s length of regular polygon inscribed in the circle with $2^n$ and $2^{n+1}$ sides respectively, $n=2, 4, ....$

Fig. 1

On one hand, we see the area of $\Delta ABC$ as

$\frac{1}{2}\cdot AB\cdot BC = \frac{1}{2}\cdot AB\cdot L_{n+1}$.

On the other hand, it is also

$\frac{1}{2}\cdot AC\cdot BE = \frac{1}{2}\cdot 2r\cdot \frac{L_n}{2}=\frac{1}{2}\cdot r\cdot L_n.$

Therefore,

$\frac{1}{2}AB\cdot L_{n+1}= \frac{1}{2}r\cdot L_n.$

Or,

$AB^2\cdot L_{n+1}^2 = r^2\cdot L_n^2\quad\quad\quad(1)$

where by Pythagorean theorem,

$AB^2= (2r)^2 - L_{n+1}^2.\quad\quad\quad(2)$

Substituting (2) into (1) gives

$(4r^2-L_{n+1}^2)L_{n+1}^2 = L_n^2\implies 4r^2L_{n+1}^2 - L_{n+1}^4 = r^2 L_n^2.$

That is,

$L_{n+1}^4-4r^2L_{n+1}^2+r^2 L_n^2 = 0.$

Let $p = L_{n+1}^2$, we have

$p^2-4r^2 p + r^2 L_n^2=0.\quad\quad\quad(3)$

Solving (3) for $p$ yields

$p = 2r^2 \pm r \sqrt{4 r^2-L_n^2}.$

Since $L_n^2$ must be greater than $L_{n+1}^2$ (see Exercise 1), it must be true (see Exercise 2) that

$L_{n+1}^2=2r^2 - r \sqrt{4r^2-L_n^2}.\quad\quad\quad(4)$

Notice when $r=\frac{1}{2}$, we obtain (5) in “Truth vs. Intellect“.

With increasing $n$,

$L_n\cdot 2^n \approx \pi\cdot 2r \implies \pi \approx \frac{L_n 2^n}{2r}.\quad\quad\quad$

We can now compute the approximate value of $\pi$ from any circle with radius $r$:

Fig. 2 $r=2$

Fig. 3 $r=\frac{1}{8}$

Exercise 1 Explain $L_{n}^2 > L_{n+1}^2$ geometrically.

Exercise 2 Show it is $2r^2-r\sqrt{4r^2-L_n^2}$ that represents $L_{n+1}^2.$

# Truth vs. Intellect

It was known long ago that $\pi$, the ratio of the circumference to the diameter of a circle, is a constant. Nearly all people of the ancient world used number $3$ for $\pi$. As an approximation obtained through physical measurements with limited accuracy, it is sufficient for everyday needs.

An ancient Chinese text (周髀算经,100 BC) stated that for a circle with unit diameter, the ratio is $3$.

In the Bible, we find the following description of a large vessel in the courtyard of King Solomon’s temple:

He made the Sea of cast metal, circular in shape, measuring ten cubits from rim to rim and five cubits high, It took a line of thirty cubits to measure around it. (1 Kings 7:23, New International Version)

This infers a value of $\pi = \frac{30}{10} = 3$.

It is fairly obvious that a regular polygon with many sides is approximately a circle. Its perimeter is approximately the circumference of the circle. The more sides the polygon has, the more accurate the approximation.

To find an accurate approximation for $\pi$, we inscribe regular polygons in a circle of diameter $1$. Let $L_{n}, L_{n+1}$ denotes the side’s length of regular polygon with $2^n$ and $2^{n+1}$ sides respectively, $n=2, 4, ....$

Fig. 1

From Fig. 1, we have

$\begin{cases} L_{n+1}^2 = x^2 + (\frac{1}{2} L_n)^2\quad\quad\quad(1) \\ (\frac{1}{2})^2 = (\frac{1}{2}L_n)^2 + y^2\quad\quad\;\quad(2)\\ x+y = \frac{1}{2}\;\quad\quad\quad\quad\quad\quad(3) \end{cases}$

It follows that

$y\overset{(2)}{=}\sqrt{(\frac{1}{2})^2-(\frac{1}{2} L_n)^2} \overset{(3)}{ \implies} x=\frac{1}{2}-\sqrt{(\frac{1}{2})^2-(\frac{1}{2}L_n)^2}.\quad\quad\quad(4)$

Substituting (4) into (1) yields

$L_{n+1}^2 = \left(\frac{1}{2}-\sqrt{(\frac{1}{2})^2-(\frac{1}{2}L_n)^2}\right)^2+(\frac{1}{2}L_n)^2$

That is,

$L_{n+1}^2 = \frac{1}{4}\left(L_n^2 + \left(1-\sqrt{1-L_n^2}\right)^2\right).$

Further simplification gives

$L_{n+1}^2 = \frac{1}{2}\left(1-\sqrt{1-L_n^2}\right),\quad\quad\quad(5)$

Starting with an inscribed square $(L_2^2 =\frac{1}{2})$, we compute $L_{n+1}^2$ from $L_{n}^2$ (see Fig. 2). The perimeter of the polygon with $2^{n+1}$ sides is $2^{n+1} \cdot L_{n+1}$.

Fig. 2

Clearly,

$\lim\limits_{n \rightarrow \infty} 2^n \cdot L_{n} = \pi$.

Exercise-1 Explain, and then make the appropriate changes:

Hint: (5) is equivalent to $L_{n+1}^2 = \frac{L_n^2}{2\left(1+\sqrt{1-L_{n}^2}\right)}.$